Summary of the proceedings of the Provincial Synod of New South Wales. - Church of England in Australia. Province of New South Wales. Synod ([Sydney : The Synod], 1965)
Includes the Synod sermon and index.
Keywords: Church of England in Australia. -- Province of New South Wales -- Periodicals; Church of England in Australia. -- Province of New South Wales -- Congresses; Australian